Neuroprotection Against NMDA-Induced Retinal Damage by Philanthotoxin-343 Involves Reduced Nitrosative Stress - Mohamad, Mohamad Haiqal Nizar; Abu, Izuddin Fahmy; Fazel, Muhammad Fattah; Agarwal, Renu; Iezhitsa, Igor; Juliana, Norsham; Mellor, Ian R.; Franzyk, Henrik (Frontiers in Pharmacology, 2021)
N-methyl-D-aspartate receptor (NMDAR) overstimulation is known to mediate neurodegeneration, and hence represents a relevant therapeutic target for neurodegenerative disorders including glaucoma. This study examined the neuroprotective effects of philanthotoxin (PhTX)-343 against NMDA-induced retinal injury in rats. Male Sprague Dawley rats were divided into three groups; group 1 received phosphate buffer saline as the negative control, group 2 was injected with NMDA (160 nM) to induce retinal excitotoxic injury, and group 3 was pre-treated with PhTX-343 (160 nM) 24 h before NMDA exposure. All treatments were given intravitreally and bilaterally. Seven days post-treatment, rats were subjected to visual behaviour assessments using open field and colour recognition tests. Rats were then euthanized, and the retinas were harvested and subjected to haematoxylin and eosin (H&E) staining for morphometric analysis and 3-nitrotyrosine (3-NT) ELISA protocol as the nitrosative stress biomarker. PhTX-343 treatment prior to NMDA exposure improved the ability of rats to recognize visual cues and preserved visual functions (i.e., recognition of objects with different colours). Morphological examination of retinal tissues showed that the fractional ganglion cell layer thickness within the inner retina (IR) in the PhTX-343 treated group was greater by 1.28-fold as compared to NMDA-treated rats (p < 0.05) and was comparable to control rats (p > 0.05). Additionally, the number of retinal cell nuclei/100 μm2 in IR for the PhTX-343-treated group was greater by 1.82-fold compared to NMDA-treated rats (p < 0.05) and was comparable to control group (p > 0.05). PhTX-343 also reduced the retinal 3-NT levels by 1.74-fold compared to NMDA-treated rats (p < 0.05). In conclusion, PhTX-343 pretreatment protects against NMDA-induced retinal morphological changes and visual impairment by suppressing nitrosative stress as reflected by the reduced retinal 3-NT level.